Functional Adrenocortical Adenoma in a Child with Beckwith–Wiedemann Syndrome. (6th August 2021) - Doya, Leen Jamel; Hassan, Naya Talal; Mansour, Hanin Ahmed; Alkhalil, Mohammad Ahmad Almahmod; Alkhalil, Abdul Alrahman Almahmod; Mansour, Nada; Abdallah, Alaa
Abstract : Beckwith–Wiedemann syndrome (BWS) is a rare congenital condition characterized by complex overgrowth of different body parts. Children with Beckwith–Wiedemann syndrome, particularly those with hemihypertrophy, experience an increased risk of developing benign and malignant tumors. This case report presents an 18-month-old girl with features suggestive of Beckwith–Wiedemann syndrome who developed pubic hair, high levels of testosterone, and DHEAS with normal cortisol and progesterone levels. Computed tomography revealed a left adrenal mass. Histopathological examination of the resected mass showed an adrenocortical tumor. Her postoperative evaluation showed normal testosterone and DHEAS levels. Early diagnosis and detection of intra-abdominal neoplasms in infants with Beckwith–Wiedemann syndrome are essential to avoid serious clinical complications.